A Phenomenological Study of the Implementation of Problem Based Learning in Reading Comprehension Learning of Fourth Grade Students at SD Negeri Kaliurang 1 - Ratih Widya Utami; Muhardila Fauziah (Journal of Educational Sciences, 2026)
Reading literacy remains a major challenge for elementary school students, particularly in identifying main ideas and understanding implicit information. This study aimed to explore the experiences of fourth-grade students at SD Negeri Kaliurang 1 in learning reading comprehension through the Problem Based Learning (PBL) model. A qualitative phenomenological approach was employed with seven purposively selected students. Data were collected through in-depth interviews, observations, and document analysis, then analyzed using the Miles and Huberman model. The findings revealed three main themes: students’ learning experiences, the meanings they constructed from the learning process, and the supporting and inhibiting factors of PBL implementation. Initially, students experienced confusion but gradually became more active, independent, and confident in expressing ideas. They also developed greater awareness of reading comprehension as a collaborative and reflective process. Supporting factors included peer collaboration, teacher guidance, contextual learning materials, and sufficient learning time. Meanwhile, differences in reading ability, passive learning habits, limited learning media, and low self-confidence were identified as obstacles. Overall, the study concludes that the PBL model provides more meaningful, active, and collaborative learning experiences than conventional instruction while fostering students’ reading comprehension and metacognitive awareness.